Can radiological findings detect neuropathic pain in patients with osteoarthritis of the knee undergoing surgery?. (14th February 2023) - Ogawa, Hiroyasu; Nakamura, Yutaka; Sengoku, Masaya; Shimokawa, Tetsuya; Sohmiya, Kazuki; Ohnishi, Kazuichiro; Matsumoto, Kazu; Akiyama, Haruhiko
Objectives: The mechanism underlying neuropathic pain (NP) in osteoarthritis (OA) of the knee is not completely understood. This study aimed to investigate whether possible NP in patients with knee OA undergoing knee surgery is associated with specific radiological findings. Methods: This study included 197 patients who underwent knee surgery for symptomatic knee OA. Clinical evaluation was performed using the Central Sensitization Inventory (CSI), Western Ontario and McMaster Universities Arthritis Index (WOMAC), and PainDETECT questionnaire. Radiological evaluation was performed using the hip-knee-ankle (HKA) angle, posterior tibial slope (PTS), varus and valgus laxities, and magnetic resonance imaging OA Knee Score (MOAKS). Radiological findings were compared between patients with possible and unlikely NP. Logistic regression analysis was performed to identify the predictive factors for NP. Results: There were 163 and 34 patients with unlikely NP and with possible NP, respectively. The percentage of patients with CSI score ≥ 40 was significantly higher in the possible NP group than in the unlikely NP group (17.6% vs. 6.1%). Patients with possible NP had worse WOMAC scores than patients with unlikely NP. There were no significant positive associations between the possible NP and radiological findings in knee OA. Regression analysis showed no predictive factors for possible NP. Conclusions: Possible NP is not associated with specific radiological findings in knee OA. Patients with possible NP may mediate CS and experience more severe symptoms, including decreased knee function and lower quality of life, than patients with unlikely NP.